1967
DOI: 10.1063/1.1709769
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of Polymer Droplets

Abstract: The nucleation of droplets of polyethylene, polyethylene oxide, polym''Ymethylene, nylon 6, poly (3,3bis-chloromethyloxacYclobutane), isotactic polypropylene, and isotactic polystyrene, suspended in silicone oil, has been investigated. Under conditions of slow cooling (0.1 °C/min), two different phenomena were observed; occasional droplet solidification at low degrees of subcooling, the number of droplets solidified and the temperature at which nucleation occurred being a function of the thermal melt history; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(151 citation statements)
references
References 8 publications
10
140
1
Order By: Relevance
“…This peculiar crystallization behavior, recently described and thoroughly discussed [22] for a series of PTFE-PMMA core-shell nanoparticles, can be rationalized within the frame of the fractionated crystallization mechanism [23,24]. Due to the compartmentalization of PTFE within the core-shell nanoparticles, the number of the dispersed PTFE particles is much greater than the number of heterogeneities that usually nucleate the polymer in bulk.…”
Section: Resultsmentioning
confidence: 99%
“…This peculiar crystallization behavior, recently described and thoroughly discussed [22] for a series of PTFE-PMMA core-shell nanoparticles, can be rationalized within the frame of the fractionated crystallization mechanism [23,24]. Due to the compartmentalization of PTFE within the core-shell nanoparticles, the number of the dispersed PTFE particles is much greater than the number of heterogeneities that usually nucleate the polymer in bulk.…”
Section: Resultsmentioning
confidence: 99%
“…The recrystallization exotherm appeared at 40 8C (T c,PEO ), only 58 lower than that of the PEO control. Because the crystallization temperature of the nanolayers was close to that of the bulk and much higher than that of homogeneous nucleation, usually put between À10 and 0 8C, [19,20] it was concluded that crystallization of the PEO nanolayers nucleated on heterogeneous nuclei, such as catalyst residues, high molecular weight gel particles, or dust particles.…”
Section: Experimental Partmentioning
confidence: 98%
“…Crystallization ends at very low rate, due to depletion of crystallizable polymer and (for high crystallinity materials) to a decrease of the interfacial area caused by interference between competing growing crystals, among other reasons. Between initial and final stages, the crystallization rate reaches a maximum, at a temperature identified as crystallization temperature of the polymer 1,[28][29][30][31][32][33][34][35][36][37][38] . The cold crystallization temperature of PET samples tested increased from 110 °C when heated at 1 °C/min to 150 °C when heated at 50 °C/min.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that, under the tests conditions PS is a completely amorphous polymer, immiscible in PET; the solubility limit of PS in PET is believed to be less than 1%, thus it is possible that once the solubility limit between PET and PS to be reached PS is segregated at amorphous zone then producing little effect on the crystalline phase of PET. In literature database several explanations are presented for the multiple crystallization phenomenon: two kinds of amorphous regions, inter-lamellar and inter-spherulite, different crystalline geometries, co-crystallization and fractional crystallization, secondary or recrystallization effects 6,9,11,12,14,28,[30][31]35,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] . PET crystallization in PET/PS blends proceeds at a higher temperature and lower crystallization rate than in the neat resin.…”
Section: Resultsmentioning
confidence: 99%